GAMBARAN PENGETAHUAN IBU HAMIL TENTANG KURANG ENERGI KRONIK PADA KEHAMILAN - Alda Noviyanty; Iryanti -; Kamsatun -; Susi Kusniasih (Jurnal Kesehatan Siliwangi, 2020)
ABSTRACT This research is motivated by the prevalence of stunting in Indonesia ranked fifth in the world. Basic Research Data (Riskesdas 2018) shows the stunting prevalence is 30.8%, but the prevalence of stunting in Indonesia has not yet reached the WHO target set at 20%. Stunting can be caused by several things, one of which is the Chronic Energy Deficiency (CED) in pregnancy. Based on data obtained from the Ministry of Health in 2013 the proportion of pregnant women with CED increased from 31.3% to 38.5%. -Prevalence of CED risk in West Java is ± 20% and the prevalence of highrisk pregnant women reaches ± 35%. This indicates in West Java is still relatively high. This study aims to determine the description of knowledge of pregnant women about CED in pregnancy. This type of research is Study Literature Review by searching, research and related articles, have searched and quoted related journals from Google Scholar. Data review was conducted to draw conclusions and results on the knowledge of pregnant women about CED. The results that researchers found were as many as 3 journals related to the knowledge of pregnant women about CED. The conclusions of the 3 research journals were 23.7% - 59.5% of pregnant women with less knowledge about the CED category. Recommendations to the Nursing profession for effective promotion. One way can be done is counseling CED on pregnant women.Pregnant women will avoid CED during pregnancy and can prevent the occurrence of stunting in infants. Keywords: Knowledge, Pregnant Women, CED